1985
DOI: 10.5271/sjweh.2205
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue disorders in the upper limbs of female garment workers.

Abstract: PUNNETT L, ROBINS JM, WEGMAN DH, KEYSERLING WM. Soft tissue disorders in the upper limbs of female garment workers. Scand J Work Environ Health 11 (1985) 417-425. In this cross-sectional investigation of female garment workers the prevalence of soft tissue disorders of the hands and arms was studied. The findings were compared with the prevalence of disorders in a group of female hospital employees not required to use repetitive hand motion. One hundred and eighty-eight garment workers and 76 hospital employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
1
10

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(90 citation statements)
references
References 9 publications
12
67
1
10
Order By: Relevance
“…Oilly a few of these persons were present for the follow up study; thus the absence of significant findings regarding this aspect should not be interpreted as a negative finding but as a noninformative one. The literature is inconsistent concerning the relationship between age or years of employment as a sewing machine operator and the prevalence of symptoms of the neck and shoulders, some finding correlations ( 1 -4 , 16) and others not (5,18,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oilly a few of these persons were present for the follow up study; thus the absence of significant findings regarding this aspect should not be interpreted as a negative finding but as a noninformative one. The literature is inconsistent concerning the relationship between age or years of employment as a sewing machine operator and the prevalence of symptoms of the neck and shoulders, some finding correlations ( 1 -4 , 16) and others not (5,18,25).…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders in the neck and shoulder region are frequent among worlters performing monotonous, highly repetitive, and high-speed precision tasks (1)(2)(3)(4)(5)(6)(7). Numerous cross-sectional epidemiologic studies have identified sewing machine operators, office workers with visual display units (VDU operators), meat cutters, assembly-line workers, and the like as high-risk groups for developing musculoskeletal disorders in the neck and shoulders (7,8), and preventive strategies are needed (9-12).…”
mentioning
confidence: 99%
“…Il faut tout d'abord rappeler que ces travailleuses oeuvraient antérieurement dans l'organisation traditionnelle de travail dont l'une des principales caractéristiques est d'être assise. Or comme le confirment un assez grand nombre de recherches sur la position assise et plus particulièrement sur les opératrices de machine à coudre, cette position est accompagnée de nombreux problèm es physiologiques et musculo-squelettiques (Sjogaard et al 1988 ;Vihma, Nurminen et Mutanen 1982 ;Serratos-Perez et Mendiola-Anda 1993 ;Vézina, Tierney et Messing 1992 ;Punnett et al 1985 ;Sokas, Spiegelman et Wegman 1989 ;Brisson, Vinet et Vézina 1989 ;Blader et al 1991 ;Li, Haslegrave et Corlett 1995 ;Laville 1985). Certains, comme la pression exercée sur les disques intervertébraux, dans la région lombaire, sont mêmes plus importants en position assise que debout (Grandjean et Hunting 1977 ;Nachemson 1966 ;Yates et Karwowski 1987, 1992.…”
Section: Resultsunclassified
“…Des études ont été conçues pour mieux mesurer les types d'expositions retrouvées dans les emplois féminins (Silverstein, Fine et Armstrong 1985 ;Punnett et al 1985 ;Vézina, Tierney et Messing 1992 ;Dumais et al 1993 ;Messing et al 1998). La relation entre expositions domestiques et professionnelles dans la détermination de la fatigue, la dépression, les douleurs musculo-squelettiques et les troubles cardiovasculaires a fait l'objet de plusieurs études (Romito 1994 ;Brisson et al 1999 ;Bjorkstén et al 2001).…”
Section: Nous Avons Analysé Le Rapport Annuel Produit En 1999 Par L'iunclassified